Efficacy, Safety, and Retention Rate of Extended-Release Divalproex Versus Conventional Delayed-Release Divalproex: A Meta-Analysis of Controlled Clinical Trials - Zhang, Chen Qi; Li, Hong Yan; Wan, Yong; Bai, Xue Yang; Gan, Lu; Wang, Juan; Sun, Hong Bin (Frontiers in Pharmacology, 2022)
Purpose: A novel once-daily divalproex-extended release (ER) dose formulation has been developed, which prolongs therapeutic serum levels compared with that of twice-daily conventional divalproex-delayed release (DR) . This study aims to systematically examine and compare the efficacy, safety, and retention rate of ER divalproex (VPA-ER) and conventional DR divalproex (VPA-DR). Methods: RCTs reporting the efficacy, adverse events (AEs) and medicine compliance of ER and DR divalproex were searched in online databases, including the PubMed, Embase and Cochrane Library databases via searching Mesh words and term words. Observational studies with potential bias were excluded. The meta-analysis was performed using Stata16.0 software. Findings: A total of 13 RCTs, involving 1028 participants were included in this meta-analysis. Efficacy ,AEs and the drug retention rate were the main study outcomes. According to our study, VPA-ER presented clinical significance in the population with bipolar disorders (BD) compared to placebo (39.5% vs 27.2%, P<0.001). While similar efficacy of VPA-ER and VPA-DR were observed in epilepsy patients to controlling seizures (87.4% vs 86.5%, P=0.769). A significantly lower incidence of AEs was reported between VPA-ER group and placebo group (26.8% vs 34.8%, P=0.003). By contrast, there is no evidence of a difference in safety between VPA-ER and VPA-DR (29.4% vs 30.5%, P=0.750). Besides, drug retention rate was significantly inferior in VPA-ER group than placebo group (76.0% vs 82.7%, P=0.020), especially in migraine patients (P=0.022) and in patients which treated for shorter than 4weeks (P=0.018). Implications: The efficacy of VPA-ER is significantly superior to placebo treatment, which provides a similar efficacy as conventional VPA-DR. VPA-ER is well tolerated with a low rate of AEs to that associated with placebo. Besides, the acceptable medicine compliance of VPA-ER is conducive to the long-term maintenance treatment of chronic diseases. Although we analyzed open-labels and crossover design RCTs, large-scale multi-center studies on the efficacy and medicine compliance of new ER formulations with less AEs are needed to be investigated in the future to validate our conclusion.